Treating lupus patients with antimalarials: analysis of safety profile in a single-center cohort. (September 2018) - Spinelli, F R; Moscarelli, E; Ceccarelli, F; Miranda, F; Perricone, C; Truglia, S; Garufi, C; Massaro, L; Morello, F; Alessandri, C; Valesini, G; Conti, F
This longitudinal retrospective study aims at describing the safety profile and the reasons for discontinuation of antimalarials in patients with systemic lupus erythematosus (SLE) and discoid lupus erythematosus (DLE), focusing on ocular toxicity. We analyzed the clinical data of 845 SLE and DLE patients; 59% of them were taking antimalarials: 1.4% chloroquine (CQ), 88.5% hydroxychloroquine (HCQ) and 10.1% both. The mean therapy duration was 82.5 ± 77.4 months. At least one side effect was reported by 19.4% of patients, leading to temporary or permanent withdrawal in 9.1% and 10.3% of cases, respectively; 19.3% of patients experienced side effects with HCQ and 8.6% with CQ. In 55.1% of cases, the adverse event was mild or moderate. Ophthalmological alterations were reported by 8.5% but were confirmed by the ophthalmological examination in 5.5% of cases. Retinal alterations were associated with age, disease duration and duration of the antimalarial therapy, but not to drug dose and comorbidities or lupus nephritis. This is the largest monocentric longitudinal study confirming the good safety profile of antimalarials in DLE and SLE patients. The main adverse events during the therapy were mild or moderate, but maculopathy—reported in a low percentage of patients—remains the main cause of treatment withdrawal.